1997
DOI: 10.1037/0735-7028.28.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Supervision of psychological assessment: A developmental model.

Abstract: The supervision of assessment has been greatly neglected in the literature. A model of supervisee development, from novice tn master assessor, is presented. The model focuses on the development of the ability to integrate data into a coherent formulation of the person being tested. Appropriate supervision depends on a matching of the supervisor's behavior to the supervisee's needs, as specified by the supervisee's current level of development. This development is dramatized by improvements in interpreting spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 2 publications
(2 reference statements)
1
28
0
Order By: Relevance
“…It is recommended that this training occur through a combination of participation, observation, and review of written reports to supervise the evaluations conducted by the trainees (Dumont & Willis, 2004). An important component to the final stage of this process is encouraging the supervisee to step into the supervisory role in order to further develop and refine his or her assessment practices (Finkelstein & Tuckman, 1997). In the current article, we address this call to "pass the torch" in the final stage of assessment training by focusing specifically on how supervisory skills in assessment are developed (Finkelstein & Tuckman, 1997).…”
Section: Training Models For Assessment Supervisionmentioning
confidence: 97%
See 4 more Smart Citations
“…It is recommended that this training occur through a combination of participation, observation, and review of written reports to supervise the evaluations conducted by the trainees (Dumont & Willis, 2004). An important component to the final stage of this process is encouraging the supervisee to step into the supervisory role in order to further develop and refine his or her assessment practices (Finkelstein & Tuckman, 1997). In the current article, we address this call to "pass the torch" in the final stage of assessment training by focusing specifically on how supervisory skills in assessment are developed (Finkelstein & Tuckman, 1997).…”
Section: Training Models For Assessment Supervisionmentioning
confidence: 97%
“…Second, although others have identified challenges in supervising assessment training, including administration errors and fidelity (Callahan, 2015;Loe et al, 2007) and have proposed suggested remedies, the comprehensive implementation of these solutions has not been explored in any explicit assessment approach. Third, while some models of training have recognized the importance of demonstrating skill in the supervision of clinical assessment as part of establishing competency in this domain (Finkelstein & Tuckman, 1997), a practical approach for developing competency specifically in supervisory skills is lacking. We address these limitations in describing our approach.…”
Section: Training Models For Assessment Supervisionmentioning
confidence: 99%
See 3 more Smart Citations